Learner’s Engagement through Multi-layer Concept Map in Science Learning: A STEAM Perspective - Parajuli, Dilu Ram (Interdisciplinary Research in Education, 2024)
This research focuses on the empirical investigation of STEAM literacy as encompassing techniques derived from implementing multi-layer concept map techniques in the science classroom. As a pedagogical tool for student learning and teacher instruction, it offers students more significant opportunities to expand their understanding of and gain engaging experiences in multidisciplinary areas like STEAM subjects. It also enhances the learner’s own choice of concept and shares the designed concept map with/within the group accompanied by dialogic scenarios. Methodologically, it is based on participatory action research (PAR), and it is a qualitative-dominated mixed design, which tries to promote expanded interest and self-directed technological and artistic learning practices in science through the perspective of STEAM literacy. The meaning-making process through the genre of interpretations is directly tested in the field of action and observation and the Likert scale-based reflective statements make results more trustworthy. Embedded in the consequences of overall data is the fact that STEAM literacy practices are developed in the science classroom through this tool. Due to PAR and more engagement of learners, it enhances a variety of diverse learning opportunities and sharpens learners’ independent thinking, creativity, and action.